Does Improvement in Respiratory Function after Hemodialysis Correlate with Ultrafiltration Volume? - Shakireen, Najmush; Amir, Muhammad; Arshad, Abdul Rehman; Abideen, Zain ul; Ullah, Sobia Zaheer; Ihtesham, Rabeea (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To evaluate the effect of mechanical ultrafiltration on improvement in respiratory functions among patients of end-stage renal disease dependent on hemodialysis. Study design: Cross-sectional analytical study. Place and Duration of Study: Dialysis Unit, Combined Military Hospital Peshawar, Pakistan, from Sep to Nov 2021 Methodology: Patients on maintenance hemodialysis for at least three months were included. Patients with altered mental status and gross rheumatological abnormalities and unwilling patients were excluded. Spirometry was done before and after mid-week dialysis sessions thrice at two minutes intervals and the best values recorded. Different spirometry parameters before and after dialysis session were compared. The relationship of changes in these parameters with ultrafiltration volumes was also examined. Results: A total of 50 patients were enrolled of which 36(72%) were females and 14(28%) were males. The mean age was 48.76±11.72 years. Low and high ultrafiltration groups included 26 and 24 patients, respectively. The median ultrafiltration volume was 1.5(1.00-2.80) liters. The majority of the patients showed restrictive pattern. The mean FEV1 percentage was 48.87±17.35 and 57.94±75.34 before and after hemodialysis respectively (p=0.387). The mean FVC percentage was 50.62±19.28 and 46.04±18.73 before and after the hemodialysis respectively (p=0.056). FEV1/FVC percentage was significantly different before and after hemodialysis i.e.106.7±24.0 and 113.30±16.94, respectively (p=0.014). Conclusion: Lung parameters improved slightly in patients after dialysis. However, ultrafiltration volume did not have significant change on any of the measured parameters.